2017
DOI: 10.2106/jbjs.15.00917
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Taper Failure in a Contemporary Metal-on-Metal Hip Arthroplasty System Through Examination of Unused and Explanted Prostheses

Abstract: This study shows evidence that previously unappreciated variations in manufacturing processes may have a major impact on the clinical outcomes of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…A total of 10 measurements on each articulating sample were acquired using a 10× objective lens and 2.0× manual zoom (area of view 317 × 238 μm). A two‐dimensional (2D) contacting profilometer (Mitutoyo Surftest SJ‐210) was used for the surface roughness (Ra) analysis of the tapers and trunnions in both tests . Six linear scans for each taper and trunnion were performed with a cut off length of 0.8 mm, giving each scan a total roughness evaluation trace length of 4.0 mm .…”
Section: Methodsmentioning
confidence: 99%
“…A total of 10 measurements on each articulating sample were acquired using a 10× objective lens and 2.0× manual zoom (area of view 317 × 238 μm). A two‐dimensional (2D) contacting profilometer (Mitutoyo Surftest SJ‐210) was used for the surface roughness (Ra) analysis of the tapers and trunnions in both tests . Six linear scans for each taper and trunnion were performed with a cut off length of 0.8 mm, giving each scan a total roughness evaluation trace length of 4.0 mm .…”
Section: Methodsmentioning
confidence: 99%
“…There is a wide variation in the manufacturing tolerances of the taper and trunnion angles of THRs. Langton et al (2016) showed taper angles ranged from 5°32´ to 5°42´ for 93 "Articuleze" (DePuy) femoral heads. Brock et al (2015) showed a range of 5°56´ to 6°9´ for S-ROM (DePuy) trunnion angles and 5°33´ to 5°47´ for Corail (DePuy) trunnion angles.…”
Section: Finite Element Wear Analysismentioning
confidence: 99%
“…Langton et al (2012) have shown varus stems, larger head diameters and head offsets increase the horizontal moment arm acting at the taper junction, which increases the fretting wear rate at this junction. They further showed a wide variation in the manufacturing tolerances of the taper and trunnion angles of one manufacturer's THRs (Langton et al, 2016). They analysed 93 retrieved head tapers and found that many of the tapers had not been manufactured to specifications.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many advantages of femoral component modularity, it introduces another contact interface which may lead to wear particle generation. Recently, many reports have identified THR failure with taper junction wear (Brock et al, 2015;Crowninshield et al, 2004;Esposito et al, 2014;Kop et al, 2012;Langton et al, 2012;Langton et al, 2016;Langton et al, 2008;Lavigne et al, 2011;Panagiotidou et al, 2013;Smith et al, 2005). This is fretting wear and is a result of contact stress and relative micromotion at the taper-trunnion interface of THRs (Delaunay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%